THE ASSOCIATION OF THE NEUROLOGICAL SYMPTOMS OF COVID-19 INFECTION WITH PATIENT HOSPITALIZATION IN IRAQI KURDISH PATIENTS - Al-Bajalan, Sarwer Jamal Al-Bajalan (Journal of Sulaimani Medical College, 2024)
Background Coronavirus disease-2019 (COVID-19) can affect multiple organs, including central and peripheral nervous systems, with various neurological manifestations Objectives To determine the frequency of neurological manifestations in patients with COVID-19 infection and identify their association with hospitalization. Materials and Methods An observational cross-sectional study was conducted on 351 COVID-19-infected patients in Sulaimaniyah, Iraq. The frequency of the neurological symptoms was determined and correlated with the hospitalization rate. Results The specific neurological symptoms were more predominant in hospitalized patients (98.2%) than non- hospitalized (93.4%) (p=0.052). Insomnia (72%), confusion (38.1%), urinary incontinence (14.9%), fecal incontinence (8.9%), and seizures (6.0%) were associated with hospitalization (p=0.008, p=0.003, p=0.003, p=0.023, and p=0.027, respectively). While, loss of smell, feeling of debility, loss of balance and hypersomnia were significantly observed in non-hospitalized patients (p≤0.05). The nonspecific neurological symptoms did not significantly differ between groups (p=0.240). However, headache (75.4%), fatigue (72.1%) and backache (68.3%) were associated with non-hospitalization (p<0.001), while constipation (32.75%) and vomiting (24.4%) were associated with hospitalization (p=0.002 and p=0.015, respectively). The most common symptom among patients was neurological (n=204, 58.1%) associated with less hospitalization. Conclusion There was a significant association between neurological symptoms (insomnia, confusion, urine/fecal incontinence, seizures, constipation, and vomiting) and the rate of hospitalization. Loss of smell, weakness/ debility, loss of balance, hypersomnia, headache, fatigue, and backache were more common in non-hospitalized patients.
Keywords: COVID19 infection; hospitalization rate; specific neurological symptoms; crosssectional study